Measurement And Analysis Of Physical Properties Of Major Rocks In North West Peninsular Malaysia - Musa, Mohd Hafiz (2012)
All geophysical methods, either in the exploration of natural resources or in the study of earth structures are related to the physical properties of rocks. Physical properties of the most commonly used in geophysical research are the property of elasticity, specific gravity (or density) and compressive strength. These physical properties are the basis for the interpretation of data collected from studies of geophysical research. The research has three objectives. Firstly, to study the physical parameters of Malaysia’s major rock in terms of property of elasticity, specific gravity or density and compressive strength. Secondly, to examine the relationship between all the physical parameters under investigation, and thirdly to form a table of physical characteristics of these three types of rock (granite, limestone and marble). All rock samples were collected from the North West peninsular Malaysia and three types of tests had been conducted which include method of ultrasonic testing, water displacement method, and point-load test. In general, all the results obtained in this study were validated statistically based on small ratio between mean and standard deviation. The study shows that the seismic P wave velocity, (Vp) is the highest in limestone rock than granite and marble. This result is supported by the specific gravity values which indicate that the limestone is denser than granite and marble. Correlations were made between the variations of Vp toward elastic constant. In general, there is a linear relationship between Vp with all the elastic constants and the relationship had been validated by the linear correlation coefficient, (r).